THE IDEA OF SUSTAINABLE DEVELOPMENT AND A UNIVERSITY'S SOCIAL RESPONSIBILITY – THE MOST IMPORTANT CHALLENGES - Charchuła, Jarosław (Educological discourse, 2022)
Multicontextual social changes expressed in the permanent creation of contemporary society, the specificity of qualitatively new transformations in the relationship between globality and locality, society and the subject – are not without significance for the quality of considerations on social responsibility, including university social responsibility. The term "sustainable development" is very popular today and it has made a quick career in the social sciences. In scientific research and in economic projects, it sets the direction of changes in which the inevitability of civilization development will not cause environmental degeneration. "Sustainable development" functions as a term, concept and idea to be implemented in specific actions of states, nations and social groups. This article takes up these issues and proposes some solutions as a voice in an important discussion, because it concerns the social responsibility of the university.